SMOG AND MENTAL HEALTH IN PAKISTAN (Contemporary Journal of Social Science Review, 2025)
This article examines the adverse effects of smog on the mental health of residents in Pakistan. Evidence suggests that extreme weather conditions can harm individuals both physically and mentally, leading to increased risks of depression and post-traumatic stress disorder (PTSD) (Hayes et al., 2018). Gradual climatic changes, such as rising temperatures, increasing particulate matter (PM2.5 and PM10), and declining air quality, also contribute to deteriorating mental health outcomes (World Health Organization [WHO], 2021). Smog, a recurring issue in Pakistan, affects large segments of the population, necessitating research to quantify its impacts and develop effective mitigation and treatment strategies.